China's community-based crisis management model for COVID-19: A zero-tolerance approach - Shangguan, Ziheng; Wang, Mark Yaolin (Frontiers in Public Health, 2022)
At present, the zero-tolerance and co-existence approaches are the two basic concepts used to manage COVID-19. With the increase in vaccination rates and the continuing impact of the pandemic on people's lives, the co-existence approach has become the mainstream global practice. However, its high infection rate is still an inevitable fact. China was the first country to adopt the zero-tolerance approach to deal with COVID-19 and successfully control it. Due to its immediate effects and low infection rates, this approach has been used in China until now. Through the co-operation of the government and community, China has achieved precise regional lockdowns and patient identification. This article uses the CBCM model to interpret how China has achieved its zero-tolerance approach. Finally, the secondary hazards and applicability of China's CBCM model are discussed. This article draws the following conclusions: (1) China's CBCM basically replicates Singapore's crisis management model for SARS. With the co-operation of the community, it achieved universal coverage of prevention, detection and control; (2) Government leadership in dealing with major crises is very important; (3) In addition to relying on the extreme power of the government to realize China's CBCM model, the two major factors of a submissive society and collectivism have played an important role; (4) China's CBCM model is essentially an excessive anti-pandemic strategy.